Biodiversity in the Andean Mountains: Two new rain frogs of the genus Pristimantis (Anura: Craugastoridae) from the northern Cordillera Central in Colombia - Rivera-Correa, Mauricio; González-Durán, Gustavo A.; Saldarriaga-Gómez, Ana M.; Duarte-Marín, Sebastián (Zootaxa, 2021)
Frequent biodiversity sampling and monitoring programs often lead to relevant taxonomic findings. Here, as a product of different field expeditions to two places in the northern Andes, we discover and describe two new species of rain frogs of the genus Pristimantis from the cloud forests of the Central Cordillera of Colombia. Pristimantis chocolatebari sp. nov. is diagnosed by having the following character states: dentigerous process of vomer triangular, snout large and protruding, dorsum smooth, vocal slits and vocal sac present, groin and hidden part of the thighs yellow. Pristimantis carylae sp. nov. is diagnosed by having iris copper red, dentigerous process of vomer oval, snout short and rounded, dorsum finely shagreen with scattered tubercles, double nuptial pad in males, groin and hidden part of thighs pink. We also infer, for the first time, the phylogenetic position of P. permixtus, P. platychilus, and two candidate new species. In addition, we emphasize not to use genetic distance as the only source of evidence for species delimitation, considering the high intraspecific diversity found in one of the species described here. Finally, we highlight the relevance of different habitat and ecosystem conservation strategies to promote amphibian diversity studies in the Andes.